Diskrepansi Ukuran Gigi Berdasarkan Analisis Bolton Pada Pasien Ortodonti RSGM-P FKG Universitas Trisakti 2020-2024 - Muthia Zahra, Alifya; Zen, Yuniar (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: The balance of tooth size between the upper and lower arches plays an important role in achieving ideal occlusion, maintaining the stability of orthodontic treatment results, and supporting facial aesthetics. Tooth size discrepancy (TSD) can influence the success of orthodontic treatment. The Bolton analysis is commonly used to evaluate the mesiodistal width compatibility of permanent teeth between the maxilla and mandible. Objectives: To determine the tooth size discrepancy based on Bolton analysis in orthodontic patients at RSGM-P FKG Trisakti University from 2020 to 2024. Methods: This was a descriptive observational study with a cross-sectional design. Data were collected using a consecutive sampling technique from orthodontic patient records in the academic clinic archive of RSGM-P FKG Trisakti University. A total of 68 study models that met the inclusion and exclusion criteria were measured using digital calipers and analyzed using the Bolton ratio formula with a ratio scale. Results: The results of this study showed that the mean overall ratio was 92.2 ± 2.80, and the mean anterior ratio was 79.4 ± 3.20. These values indicate a general tendency of tooth size discrepancy between the maxillary and mandibular arches in the sample studied. Conclusion: The majority of patients exhibited tooth size discrepancies based on Bolton analysis. Therefore, evaluation of both anterior and overall ratios should be an important consideration in orthodontic treatment planning.